Electrocatalysts for CO2 reduction, their preparation methods and applications
Patent Information
- Application Number
- CN202610192186.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-02-10
AI Technical Summary
然而,现有催化剂体系仍面临以下问题:1)催化效率与选择性不足:整体催化活性尚不理想,限制了生产效率,反应过程中除生成目标产物CO外,常伴随产生氢气(H2)、甲烷(CH4)、甲酸(HCOOH)等多种副产物,降低了CO的选择性,增加了产物分离和提纯的难度与成本;2)稳定性不高:在电催化反应条件下,催化剂易受电极电位、电解质等因素影响,发生结构变化、表面中毒、活性组分溶出、颗粒团聚或脱落等现象,导致其活性和选择性随时间明显衰减;3)成本过高:高活性组分通常为银(Ag)等贵金属,其价格昂贵,若催化剂失活后无法有效再生,频繁更换将带来高昂成本
[0030] According to the application of this application, the electrocatalytic CO2 reduction catalyst exhibits high selectivity, high catalytic activity, and high stability in the reaction of reducing CO2 to CO via electrocatalytic reduction. Furthermore, the CO prepared based on this catalyst can be mixed with H2 in a specific ratio to form syngas (CO/H2), which can be used in a two-step methanol production process, achieving high-value conversion of CO2. Compared to the traditional one-step thermocatalytic methanol production process, the two-step methanol production process using CO2 as the initial feedstock, based on the catalyst of this application, has significant advantages: on the one hand, the highly selective CO generation ensures high purity and stable ratio of syngas, thereby increasing methanol yield and suppressing carbon deposition losses at the source; on the other hand, compared to traditional thermocatalytic CO production, electrocatalytic CO production can be carried out at room temperature, thus reducing the overall heating requirements of the methanol production process and lowering the production cost of methanol.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_7
Abstract
Description
Technical Field
[0001] This application belongs to the field of electrocatalysis technology, specifically, it provides an electrocatalytic CO2 reduction catalyst, its preparation method, and its application. Background Technology
[0002] With the acceleration of industrialization, global carbon emissions continue to rise, leading to increasingly severe climate change and environmental problems. Against this backdrop, seeking effective technologies for the resource utilization of carbon dioxide (CO2) is of great significance. Among these, the electrocatalytic reduction of CO2 to carbon monoxide (CO) technology shows significant potential. High-purity CO, as a key chemical raw material, plays an indispensable role in the synthesis of methanol and other products; its purity directly affects the quality of the final product and production costs.
[0003] Electrocatalytic reduction technology utilizes electrical energy to directly drive the conversion of CO2 into chemical products, and its energy conversion efficiency is generally superior to that of traditional thermocatalytic processes. Moreover, compared to the high-temperature and high-pressure environment required for thermocatalysis, electrocatalytic reduction can be carried out at ambient temperature and pressure, offering advantages such as mild operating conditions and high safety. The key to this technology lies in its ability to achieve highly selective production of specific products (such as CO) by controlling reaction conditions. This is crucial for improving CO yield, ensuring its purity to meet downstream methanol synthesis requirements, simplifying subsequent separation and purification processes, and reducing the overall cost of the two-step methanol synthesis process.
[0004] Currently, the most commonly used catalysts for CO electrocatalytic production of CO include metals such as gold (Au), silver (Ag), and palladium (Pd) and their alloys, often supported on carriers in the form of nanoparticles or thin films. However, existing catalyst systems still face the following problems: 1) Insufficient catalytic efficiency and selectivity: The overall catalytic activity is not ideal, limiting production efficiency. In addition to the target product CO, the reaction often produces various byproducts such as hydrogen (H2), methane (CH4), and formic acid (HCOOH), reducing CO selectivity and increasing the difficulty and cost of product separation and purification; 2) Low stability: Under electrocatalytic reaction conditions, the catalyst is easily affected by factors such as electrode potential and electrolyte, resulting in structural changes, surface poisoning, dissolution of active components, particle agglomeration, or detachment, leading to a significant decline in its activity and selectivity over time; 3) High cost: Highly active components are usually precious metals such as silver (Ag), which are expensive. If the catalyst cannot be effectively regenerated after deactivation, frequent replacement will result in high costs.
[0005] Meanwhile, catalysts prepared by traditional chemical methods (especially those containing metals such as Ni and Cu) often face problems such as easy agglomeration of metal particles and difficulty in controlling the structure of multi-metal interfaces. The randomness in their preparation process may weaken the synergistic effect between metals, while the residual metal oxides produced by incomplete reduction will reduce conductivity and activity, intensify competition for side reactions (such as hydrogen evolution reaction), and further impair CO selectivity.
[0006] In summary, existing CO2 electrocatalysts have shortcomings in terms of high catalytic performance, operational stability, and cost. Therefore, it is necessary to develop new high-efficiency catalysts. Summary of the Invention
[0007] The purpose of this application is to provide an electrocatalytic CO2 reduction catalyst, its preparation method, and its application. The catalyst prepared in this application possesses both high CO2 catalytic activity and CO selectivity, and is characterized by high stability and low cost.
[0008] In a first aspect, this application provides a method for preparing an electrocatalytic CO2 reduction catalyst, comprising: loading a bimetallic active component onto a composite support using an atomic layer deposition process, wherein the bimetallic active component is silver and tin, and the composite support comprises graphitic nitrogen carbide nanosheets and reduced graphene oxide.
[0009] This application employs atomic layer deposition (ALD) to load silver (Ag) and tin (Sn) bimetallic active components in an atomically dispersed form onto a composite support containing graphitic carbon nitride (g-C3N4) nanosheets and reduced graphene oxide (rGO). The abundant nitrogen sites and hierarchical porous structure provided by the g-C3N4 nanosheets, combined with the high conductivity network and anti-stacking effect of rGO, synergistically enhance CO2 adsorption and mass transfer efficiency, optimize the electronic environment of the support surface, and provide stable anchoring for the active sites. Utilizing ALD technology to load Ag-Sn bimetallic components avoids the common defects of catalysts prepared by traditional chemical methods, such as metal particle agglomeration, uneven distribution, and incomplete reduction. Furthermore, the synergistic effect of Ag and Sn significantly improves the catalyst's selectivity for the target product CO. In addition, the catalyst in this application is based on an in-situ electrodeposition-based regeneration strategy, which allows the active components to be directly restored to their dispersed state and catalytic performance in the reaction system after deactivation, thereby effectively extending the catalyst's lifespan and reducing overall operating costs.
[0010] In some embodiments of this application, the mass ratio of graphitic nitrogen carbide nanosheets to reduced graphene oxide in the composite carrier is (1.5~5):1, and the atomic ratio of silver to tin in the bimetallic active component is 1:(2~3).
[0011] In some embodiments of this application, the loading amount (i.e., the mass content of the bimetallic active component) of the electrocatalytic CO2 reduction catalyst is 1% to 10%.
[0012] In some embodiments of this application, the preparation method further includes the step of preparing a composite support: mixing the graphitic carbon nitride nanosheets with a dispersion of graphene oxide (GO) and ultrasonically dispersing the mixture, followed by a hydrothermal reaction to convert GO into rGO, thereby obtaining the composite support. By forming rGO in situ on g-C3N4 nanosheets, the bonding force between the two materials can be improved, thus enhancing the stability of the catalyst.
[0013] In some embodiments of this application, the graphitic carbon nitride nanosheets are prepared by the following steps: pyrolyzing nitrogen-containing organic matter to form bulk graphitic carbon nitride; then dispersing the bulk graphitic carbon nitride in water and ultrasonically exfoliating it to form graphitic carbon nitride nanosheets.
[0014] Furthermore, the nitrogen-containing organic compound is selected from at least one of melamine, urea, thiourea, cyanamide, and dicyandiamide.
[0015] Furthermore, the pyrolysis process includes: heating the nitrogen-containing organic matter to 450-600°C at a rate of 5-10°C / min and holding it at that temperature for 3-8 hours.
[0016] Furthermore, in the ultrasonic ablation process, the concentration of the bulk graphitic carbon nitride in water is 5~10 g / L, and the ultrasonic ablation power is 150~300 W, with a time of 5~10 h.
[0017] In some embodiments of this application, the step of loading the metal active component using an atomic layer deposition process includes: (a) Deposition of the first metal atomic layer The reaction chamber containing the composite support is heated to 100-180°C, and the first metal deposition cycle is repeated 10-100 times using an inert gas as both carrier and purging gas. Each cycle includes: First, a pulse of the first metal precursor is introduced into the reaction chamber, then the reaction chamber is purged with inert gas, then a pulse of the corresponding reactant is introduced into the reaction chamber, and finally the reaction chamber is purged with inert gas. (b) Deposition of the second metal atomic layer Maintain the reaction chamber temperature at 100~180℃ and an inert atmosphere, switch to the second metal precursor, and repeat the second metal deposition cycle 10~100 times. Each cycle includes the following steps: First, a second metal precursor pulse is introduced into the reaction chamber, then the reaction chamber is purged with inert gas, then a corresponding reactant pulse is introduced into the reaction chamber, and finally the reaction chamber is purged with inert gas. (c) The product obtained in step (b) is reduced and annealed in a hydrogen-containing atmosphere to form the bimetallic active component on the composite support; wherein One of the first metal precursor and the second metal precursor is a silver precursor and the other is a tin precursor. The reactant pulse corresponding to the tin precursor is an oxygen-containing source pulse, and the reactant pulse corresponding to the silver precursor is a plasma pulse.
[0018] Furthermore, the first metal precursor is a tin precursor, and the second metal precursor is a silver precursor. Depositing tin first, followed by silver, on the composite support helps anchor silver atoms, inhibits Ag particle aggregation, enhances the interaction between the bimetallic active component and the support, and regulates the phase structure of the Ag-Sn alloy or intermetallic compound. Simultaneously, this deposition sequence improves the selectivity and catalytic stability of electrocatalytic CO2 reduction to CO, and is more compatible with the characteristics of the ALD process, thus improving the uniformity of metal deposition.
[0019] In some embodiments of this application, the silver precursor is Ag(hfac)(COD) and / or Ag(CF3COO).
[0020] In some embodiments of this application, the plasma source of the plasma pulse includes hydrogen and optional carrier gas, and the plasma power is 100~250W.
[0021] In some embodiments of this application, during the deposition of silver atomic layers, the duration of the silver precursor pulse is 0.2 to 0.8 s, the duration of the plasma pulse is 0.2 to 0.8 s, and the duration of each inert gas purging is 5 to 15 s.
[0022] In some embodiments of this application, the tin precursor is at least one of Sn(NMe2)4, SnCl4, SnCl2, and Sn(CH3)4.
[0023] In some embodiments of this application, the oxygen source of the oxygen source pulse includes water vapor and optionally a carrier gas.
[0024] In some embodiments of this application, during the deposition of tin atomic layers, the duration of the tin precursor pulse is 0.2 to 0.8 s, the duration of the oxygen source pulse is 0.2 to 0.8 s, and the duration of each inert gas purging is 5 to 15 s.
[0025] In some embodiments of this application, the inert gas is independently selected from argon, nitrogen, or helium.
[0026] In some embodiments of this application, the reduction annealing temperature is 200~400℃ and the time is 10~60min.
[0027] Secondly, this application provides an electrocatalytic CO2 reduction catalyst prepared by the preparation method described in the first aspect of this application.
[0028] In the catalyst of this application, the synergistic effect of Ag-Sn bimetallic components and g-C3N4 / rGO composite support is achieved: the atomic-level precise control of active sites by the ALD process ensures the atomic-level dispersion of Ag-Sn bimetals on the support, and Sn promotes CO2 activation while Ag optimizes CO desorption. This improves CO2 catalytic activity and CO selectivity at low potentials. At the same time, the amino, imino, and hydroxyl groups on the surface of g-C3N4 are closely linked with the carboxyl and hydroxyl groups and their conjugated carbon skeleton on the surface of reduced graphene oxide (rGO) through various interactions such as hydrogen bonds, π-π conjugation, and possible covalent bonds, jointly constructing a structurally stable and synergistically enhanced g-C3N4 / rGO composite support. This effectively inhibits the migration and aggregation of Ag-Sn components during electrochemical cycling, reduces the problem of low stability caused by metal sintering and deactivation, and extends the service life of the electrode using this catalyst.
[0029] Thirdly, this application provides the application of the electrocatalytic CO2 reduction catalyst described in the second aspect in the electrocatalytic reduction of CO2 to produce CO or in a two-step process for producing methanol from CO2, wherein the two-step process includes: The first step is the electrocatalytic reduction of CO2 to produce CO; The second step involves preparing methanol from the prepared CO via thermocatalytic hydrogenation.
[0030] According to the application of this application, the electrocatalytic CO2 reduction catalyst exhibits high selectivity, high catalytic activity, and high stability in the reaction of reducing CO2 to CO via electrocatalytic reduction. Furthermore, the CO prepared based on this catalyst can be mixed with H2 in a specific ratio to form syngas (CO / H2), which can be used in a two-step methanol production process, achieving high-value conversion of CO2. Compared to the traditional one-step thermocatalytic methanol production process, the two-step methanol production process using CO2 as the initial feedstock, based on the catalyst of this application, has significant advantages: on the one hand, the highly selective CO generation ensures high purity and stable ratio of syngas, thereby increasing methanol yield and suppressing carbon deposition losses at the source; on the other hand, compared to traditional thermocatalytic CO production, electrocatalytic CO production can be carried out at room temperature, thus reducing the overall heating requirements of the methanol production process and lowering the production cost of methanol. Detailed Implementation
[0031] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.
[0032] The "scope" disclosed in this application is defined in the form of a lower limit and / or an upper limit, whereby a given scope is defined by selecting a lower limit and / or an upper limit. This type of scope may or may not include endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form an undefined scope, and any lower limit can be combined with other lower limits to form an undefined scope, similarly, any upper limit can be combined with any other upper limit to form an undefined scope. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and can be combined with any other point or single value, or with other lower or upper limits, to form an undefined scope.
[0033] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0034] The first aspect of this application provides a method for preparing an electrocatalytic CO2 reduction catalyst, the method comprising: loading a bimetallic active component onto a composite support using an atomic layer deposition (ALD) process.
[0035] In this application, the composite support comprises graphitic nitrogen carbide nanosheets (g-C3N4 nanosheets) and reduced graphene oxide (rGO). The g-C3N4 nanosheets provide abundant metal anchoring sites and CO2 adsorption active centers, while the rGO constructs a highly conductive network to support electron transport in the reaction. As some embodiments, the mass ratio of the g-C3N4 nanosheets to rGO is (1.5~5):1, for example, 1.5:1, 1.6:1, 1.7:1, 2:1, 2.5:1, 3:1, 4:1, 5:1, etc. Compared to rGO, controlling the relative amount of g-C3N4 nanosheets to be slightly excessive can further improve the dispersion of the metal active component and the reaction mass transfer efficiency while maintaining the overall conductivity and structural stability of the catalyst.
[0036] As some preferred embodiments, the preparation method of this application further includes the following steps for preparing the composite carrier: mixing the graphitic carbon nitride nanosheets with a dispersion of graphene oxide (GO) and ultrasonically dispersing them, followed by a hydrothermal reaction to convert the graphene oxide into reduced graphene oxide (rGO), thereby obtaining the composite carrier.
[0037] Compared to directly physically mixing g-C3N4 nanosheets and rGO, the above steps, by reducing GO to rGO in situ in the presence of uniformly dispersed g-C3N4 nanosheets, can significantly enhance the interaction between g-C3N4 nanosheets and rGO, effectively suppress the aggregation of the two materials, promote electronic coupling and synergistic effects between them, and make the obtained composite carrier have stronger interfacial bonding and structural stability, while maintaining a high specific surface area.
[0038] In some embodiments, the temperature of the hydrothermal reaction is 150~200℃, such as 150℃, 160℃, 170℃, 175℃, 180℃, 190℃, etc.; this temperature range can ensure that GO is efficiently reduced while preventing hydrolysis of g-C3N4 nanosheets due to excessive temperature; the hydrothermal reaction time is 5~15h, such as 5h, 6h, 7h, 8h, 10h, 12h, etc.
[0039] In some embodiments, the graphitic carbon nitride nanosheets are prepared according to the following steps: Pyrolysis of nitrogen-containing organic matter forms bulk graphitic carbon nitride; The bulk graphitic carbon nitride is dispersed in a solvent and then ultrasonically exfoliated to form graphitic carbon nitride nanosheets.
[0040] The nitrogen-containing organic compound can be selected from at least one of melamine, urea, thiourea, cyanamide, and dicyandiamide. To further improve the structural regularity and yield of the product, melamine is preferred as the nitrogen-containing organic compound. The pyrolysis process may include heating the nitrogen-containing organic compound to 450-600°C at a rate of 5-10°C / min (e.g., 5°C / min, 8°C / min, or 10°C / min) and holding it at that temperature for 1-5 hours. As specific examples, the pyrolysis temperature can be 450°C, 480°C, 500°C, 520°C, 550°C, 565°C, 600°C, etc., and the pyrolysis time (i.e., holding time) can be 1 hour, 1.5 hours, 2 hours, 3 hours, 4 hours, 5 hours, etc. Furthermore, the pyrolysis can be carried out in a muffle furnace.
[0041] The bulk graphitic carbon nitride can be dissociated into ultrathin, large-sized two-dimensional nanosheets by ultrasonic exfoliation. Typically, the desired g-C3N4 nanosheets have an average thickness of 1–5 nm and an average lateral size of 0.5–5 μm. The nanosheet thickness can be obtained statistically by atomic force microscopy (AFM), while the lateral size can be obtained statistically by scanning electron microscopy (SEM) images.
[0042] Specific examples of solvents used in ultrasonic ablation include, but are not limited to, water, alcohol solvents (e.g., methanol, ethanol, isopropanol), N,N-dimethylformamide (DMF), or a mixture of water and alcohol, with water being the preferred solvent. Additionally, the concentration of bulk graphitic carbon nitride dispersed in the solvent can be 5-10 g / L. As some embodiments, the ultrasonic ablation power is 150-300 W, and the ultrasonic duration is 5-10 h.
[0043] To obtain dried g-C3N4 nanosheets, the preferred steps for preparing g-C3N4 nanosheets include: after ultrasonic exfoliation, centrifuging the resulting dispersion, collecting the supernatant rich in g-C3N4 nanosheets, and freeze-drying to obtain dried nanosheet powder. The centrifugation speed can be 3000~8000 rpm, for example, 3000 rpm, 5000 rpm, 6000 rpm, 8000 rpm, etc., and the centrifugation time can be 5~50 min, for example, 10 min, 20 min, 30 min, 40 min, etc.
[0044] In some embodiments, the step of loading the metal active component using an atomic layer deposition process includes: (a) Deposition of the first metal atomic layer The reaction chamber containing the composite support is heated to 100-180°C, and the first metal deposition cycle is repeated 10-100 times using an inert gas as both carrier and purging gas. Each cycle includes: First, a pulse of the first metal precursor is introduced into the reaction chamber, then the reaction chamber is purged with inert gas, then a pulse of the corresponding reactant is introduced into the reaction chamber, and finally the reaction chamber is purged with inert gas. (b) Deposition of the second metal atomic layer Maintain the reaction chamber temperature at 100~180℃ and an inert atmosphere, switch to the second metal precursor, and repeat the second metal deposition cycle 10~100 times. Each cycle includes the following steps: First, a second metal precursor pulse is introduced into the reaction chamber, then the reaction chamber is purged with inert gas, then a corresponding reactant pulse is introduced into the reaction chamber, and finally the reaction chamber is purged with inert gas. (c) The product obtained in step (b) is reduced and annealed in a hydrogen-containing atmosphere to form the bimetallic active component on the composite support.
[0045] One of the first metal precursor and the second metal precursor is a silver precursor, and the other is a tin precursor. The reactant pulse corresponding to the tin precursor is an oxygen-containing source pulse, and the reactant pulse corresponding to the silver precursor is a plasma pulse. Preferably, the first metal precursor is a tin precursor, and the second metal precursor is a silver precursor.
[0046] The silver precursor may be selected from organosilver complexes, preferably at least one of Ag(hfac)(COD) ((1,5-cyclooctadiene)(hexafluoroacetylacetonate)silver(I), CAS: 38892-25-0) and Ag(CF3COO) (silver trifluoroacetate, CAS: 2966-50-9). The tin precursor may be selected from volatile tin compounds, preferably at least one of Sn(NMe2)4 (tetra(dimethylamino)tin), SnCl4, SnCl2, and Sn(CH3)4.
[0047] In step (a), heating the reaction chamber can promote the vaporization of the metal precursor. The heating temperature can be selected according to the type of precursor, and is usually 100~180℃, such as 120℃, 140℃, 145℃, 150℃, 155℃, 160℃, 170℃, 180℃, etc.
[0048] In silver atomic layer deposition, during each cycle, the silver precursor is pulsed into the reaction chamber under an inert gas carrier to form a monolayer of silver precursor capping. The reaction chamber is then purged with inert gas to remove unreacted precursor. Finally, a plasma activation pulse provides highly reactive free radicals to cleave Ag-O bonds and reduce Ag. + To Ag 0 The volatile ligands are then removed by inert gas purging. This process is repeated to form atomically dispersed silver nanoparticles in situ on the support surface.
[0049] In silver atomic layer deposition, the pulse duration when introducing the silver precursor pulse is preferably 0.2–0.8 s, such as 0.3 s, 0.5 s, 0.7 s, or 0.8 s. This promotes deposition uniformity while suppressing carbon residue and particle sintering caused by precursor gas-phase thermal decomposition.
[0050] In silver atomic layer deposition, when a plasma pulse is introduced, the selected plasma source includes hydrogen and an optional carrier gas (such as argon); when the plasma source is a mixture of hydrogen and carrier gas, the volume fraction of hydrogen can be 5% to 20%. The plasma power is preferably 100 to 250 W, for example, 120 W, 150 W, 180 W, 220 W, etc. The plasma pulse duration is preferably 0.2 to 0.8 s, for example, 0.3 s, 0.5 s, 0.7 s, 0.8 s, etc. Each purging with an inert gas can last for 5 to 15 s, for example, 5 s, 10 s, 12 s, 15 s, etc.
[0051] Preferably, in the deposition of silver atomic layers, the number of deposition cycles is 20 to 40, such as 20, 25, 35, 40, etc.
[0052] In tin atomic layer deposition, a tin precursor is pulsed into the reaction chamber under an inert gas carrier. It undergoes ligand exchange with active sites such as hydroxyl groups on the substrate surface, forming a chemisorbed monolayer of tin species and releasing volatile byproducts. Subsequently, an inert gas is introduced for purging to thoroughly remove any remaining precursor and byproducts from the chamber. Next, a pulsed oxygen source reacts with the adsorbed layer on the surface, replacing the precursor ligands with hydroxyl groups or oxygen, thereby forming a tin-oxygen (Sn-O) network structure. Finally, an inert gas purging is repeated to remove all reaction byproducts, completing the deposition of an atomic layer of tin oxide (e.g., SnO2).
[0053] In tin atomic layer deposition, when an oxygen-containing source pulse is introduced, the selected oxygen-containing source preferably includes water vapor and an optional carrier gas (such as argon); when the oxygen-containing source is a mixture of water vapor and carrier gas, the volume fraction of water vapor can be 5% to 20%. The duration of the oxygen-containing source pulse is preferably 0.2 to 0.8 s, for example, 0.3 s, 0.5 s, 0.7 s, 0.8 s, etc.
[0054] In tin atomic layer deposition, the duration of the tin precursor pulse in each cycle is preferably 0.2–0.8 s, for example, 0.3 s, 0.5 s, 0.7 s, 0.8 s. This ensures saturated adsorption while suppressing gas-phase side reactions.
[0055] In tin atom layer deposition, the inert gas purging time for each step is 5 to 15 seconds, for example, 5 seconds, 10 seconds, 15 seconds, etc. Additionally, the temperature of the reaction chamber in tin atom layer deposition can be 100 to 180°C. The specific temperature within this range can be the same as or different from the temperature used in silver atom deposition, but is preferably the same.
[0056] Preferably, in tin atomic layer deposition, the number of deposition cycles is 40 to 100, such as 40, 45, 50, 60, 80, 100, etc.
[0057] In some embodiments, the ratio of the number of cycles in the silver atomic layer deposition to the number of cycles in the tin atomic layer deposition is 1:(2~3). Alternatively, the atomic ratio of silver to tin can be adjusted by changing the number of cycles.
[0058] In steps (a) and (b), the inert gas can typically be independently selected from argon, nitrogen, or helium.
[0059] In step (c), the product of step (b) is reduced and annealed in a hydrogen-containing atmosphere (e.g., hydrogen gas). On the one hand, the deposited tin oxide is reduced to metallic tin using hydrogen gas; on the other hand, under heating, the formed metallic tin interdiffusion with the existing silver, ultimately forming a uniformly dispersed silver-tin bimetallic active component on the surface of the composite carrier. The reduction temperature can be 200~400℃, for example 200℃, 230℃, 250℃, 260℃, 280℃, 300℃, 330℃, 350℃, 370℃, 400℃, etc.; the reduction time is 10~60 min, for example 10 min, 20 min, 30 min, 45 min, 50 min, etc. As some embodiments, the reduction annealing process includes: heating to the reduction temperature at a rate of 2~10℃ / min, and holding at the reduction temperature.
[0060] In some embodiments, the atomic ratio of silver to tin in the bimetallic active component is 1:(2~3), for example 1:2, 1:2.2, 1:2.3, 1:2.5, 1:2.8, 1:3, etc.
[0061] In some embodiments, the mass content of the bimetallic active component in the electrocatalytic CO2 reduction catalyst is 1% to 10%, for example, 2.0%, 2.5%, 3.0%, 3.3%, 3.5%, 3.7%, 4.3%, 5.0%, 5.5%, 8.0%, 9.5%, etc. The metal component content in the catalyst can be determined by inductively coupled plasma mass spectrometry (ICP-MS).
[0062] The second aspect of this application provides an electrocatalyst for CO2 reduction prepared by the method described in the first aspect of this application. Thanks to the synergistic effect of the bimetallic compound support, ALD technology ensures the orderly arrangement of the Ag-Sn bimetallic compounds on the support, exhibiting high CO selectivity and CO2 catalytic activity at low potentials. The composite support solves the problems of easy sintering and deactivation of metals and low stability, allowing deactivated electrodes to regain catalytic activity after multiple cycles, extending electrode lifespan and saving costs.
[0063] The third aspect of this application provides the application of the catalytic CO2 reduction catalyst described in the second aspect of this application in the electrocatalytic reduction of CO2 to produce CO or in the two-step process for producing methanol from CO2.
[0064] In some embodiments, the catalytic CO2 reduction catalyst can be fabricated as a catalyst electrode for use in the electrocatalytic reduction of CO2 to CO. For example, the electrocatalytic CO2 reduction catalyst, Nafion solution, and conductive agent (such as carbon black, carbon nanotubes, or graphene) can be dispersed in a solvent at a ratio of (70-90):(5-15):(5-15) to prepare a catalyst ink, which is then uniformly coated onto a current collector (such as carbon paper or titanium mesh) and dried to obtain the catalyst electrode. Furthermore, the electrocatalytic reduction reaction is carried out in an electrolytic cell. Specifically, the catalyst electrode can be used as the cathode, and the Pt / Ru / C composite material as the anode, assembled into an electrolytic cell, and an electrolyte is injected to complete the assembly of the electrolysis system. The solvent in the electrolyte can be deionized water, and the concentration of the electrolyte can be 0.2-1 mol / L. Specific examples of electrolytes include, but are not limited to, KHCO3, NaHCO3, and choline bicarbonate. As some preferred examples, the reaction voltage of the electrolytic cell is controlled at 2.0~3.5V, and the current density is 80~110mA / cm². 2 The electrocatalytic temperature is 20~50℃, and the treatment time is 1~150h.
[0065] In other embodiments, the catalytic CO2 reduction catalyst is used in a two-step CO2 methanol production process, the two steps of which include: The first step is the electrocatalytic reduction of CO2 to produce CO; The second step involves preparing methanol from the prepared CO via thermocatalytic hydrogenation.
[0066] According to some embodiments, the two-step method for preparing methanol includes the following process flow: carbon dioxide is introduced into an electrolytic cell to carry out an electrochemical reduction reaction to obtain a mixed gas containing CO; Part of the mixed gas is then returned to the electrolyzer for recycling; the remaining mixed gas is mixed with H2 in a mixer, and the molar ratio of CO to hydrogen is controlled at 1:(2~2.2). After thorough mixing, the temperature is raised to 200~300℃, and methanol is synthesized by catalytic reaction in the presence of a thermal catalyst (such as a copper-zinc-aluminum (CZA) catalyst).
[0067] Compared to the traditional one-step CO2 methanol production method, the two-step electrocatalytic and thermocatalytic method for methanol production significantly reduces energy consumption (the electrocatalytic step can operate at ambient temperature and pressure, while only the CO thermocatalytic step requires medium temperature and pressure). The purified gas has a high CO concentration, which can reduce the risk of carbon buildup and poisoning of the thermal catalyst and avoid carbon loss in the CO2 to CH3OH pathway.
[0068] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.
[0069] Preparation Example 1 This preparation example illustrates the preparation method of the g-C3N4 nanosheet powder used in the following embodiments and comparative examples.
[0070] 10 g of melamine was placed in a muffle furnace and heated to 550 °C at a rate of 5 °C / min, and calcined for 4 hours to obtain blocky g-C3N4. This blocky product was ground into powder and placed in 500 mL of deionized water. The powder was then sonicated at 150 W for 8 hours to exfoliate the nanosheets, yielding a g-C3N4 nanosheet dispersion. The dispersion was then centrifuged at 8000 r / min for 30 minutes, and the supernatant was collected and freeze-dried to obtain g-C3N4 nanosheet powder (average thickness 4 nm, average size 2 μm).
[0071] Example 1 (1) Preparation of composite carrier 3g of the obtained g-C3N4 nanosheets were added to 200mL of an aqueous dispersion of graphene oxide (GO) with a concentration of 3g / L. The mixture was ultrasonically treated at 150W for 20min using an ultrasonic cell disruptor to ensure thorough mixing. Subsequently, the mixture was transferred to a reaction vessel and hydrothermally reacted at 180℃ for 6 hours to reduce GO to rGO. After the reaction was completed, the product was filtered, washed, and dried to obtain the g-C3N4 / rGO composite support.
[0072] (2) Bimetallic atomic deposition 0.1 g g-C3N4 / rGO composite support was placed in the ALD reaction chamber. First, Sn deposition was performed at 150 °C using Sn(NMe2)4 as the tin precursor and water as the co-reactant. The deposition process consisted of 50 cycles. The procedure for each cycle was as follows: Sn(NMe2)4 was pulsed for 0.5 s, followed by argon purging for 10 s, then water vapor was pulsed for 0.5 s, and finally argon purging for 10 s.
[0073] Next, the reaction chamber was switched to contain the silver precursor Ag(hfac)(COD), and plasma-assisted ALD was performed at the same temperature to achieve Ag deposition. This process used hydrogen plasma as the reducing agent, with a deposition power set to 150W, and was repeated 20 times. The procedure for a single cycle was as follows: an Ag(hfac)(COD) pulse was introduced for 0.5 s, followed by argon purging for 10 s, then a plasma (H2) pulse for 0.5 s, and finally argon purging for 10 s.
[0074] Finally, the sample after the above deposition treatment was transferred to a tube furnace and subjected to reduction annealing in an H2 atmosphere. The annealing procedure was as follows: heating to 250°C at a heating rate of 5°C / min and holding at this temperature for 30 min to obtain the bimetallic supported catalyst Ag / Sn / g-C3N4 / rGO, denoted as ASNC-1.
[0075] According to ICP-MS testing, the total bimetallic content in ASNC-1 was 3.0 wt%, and the atomic ratio of Ag to Sn atoms was 1:2.5, which is consistent with the cycle number ratio.
[0076] Example 2 The catalyst Ag / Sn / g-C3N4 / rGO was prepared according to the method in Example 1, except that in step (1), the amount of the aqueous dispersion of graphene oxide (GO) with a concentration of 3 g / L was adjusted to 600 mL. The prepared catalyst Ag / Sn / g-C3N4 / rGO was designated ASNC-2. ICP-MS analysis showed that the total bimetallic content in ASNC-2 was 3.5 wt%, and the atomic ratio of Ag to Sn atoms was 1:2.5.
[0077] Example 3 The catalyst Ag / Sn / g-C3N4 / rGO was prepared according to the method in Example 1, except that in step (2), the number of cycles for depositing the silver precursor Ag(hfac)(COD) was controlled to be 25. The prepared catalyst Ag / Sn / g-C3N4 / rGO was designated ASNC-3. ICP-MS analysis showed that the total bimetallic content in the catalyst ASNC-3 was 3.3 wt%, and the atomic ratio of Ag to Sn atoms was 1:2.
[0078] Example 4 (1) Preparation of composite carrier Same as Example 1.
[0079] (2) Bimetallic atomic deposition 0.1 g g-C3N4 / rGO composite support was placed in the ALD reaction chamber. First, Sn deposition was performed at 180 °C using SnCl4 as the tin precursor and water as the co-reactant. The deposition process consisted of 50 cycles, with each cycle following the following procedure: Sn(NMe2)4 pulse for 0.5 s, followed by argon purging for 10 s, water vapor pulse for 0.5 s, and then argon purging for 10 s.
[0080] Next, the reaction chamber was switched to contain the silver precursor Ag(hfac)(COD), and plasma-assisted ALD of silver was performed at 180°C to achieve Ag deposition. This process used hydrogen plasma as the reducing agent, with a deposition power set to 150W, and was repeated 20 times. The procedure for a single cycle was as follows: an Ag(hfac)(COD) pulse was introduced for 0.5 s, followed by argon purging for 10 s, then a plasma (H2) pulse for 0.5 s, and finally argon purging for 10 s.
[0081] Finally, the sample after the above deposition treatment was transferred to a tube furnace for reduction annealing in an H2 atmosphere. The annealing procedure was as follows: heating to 250°C at a heating rate of 5°C / min and holding at this temperature for 30 min to obtain the bimetallic supported catalyst Ag / Sn / g-C3N4 / rGO, denoted as ASNC-4. ICP-MS analysis showed that the total bimetallic content in ASNC-4 was 3.4 wt%, and the ratio of Ag to Sn atoms was 1:2.5.
[0082] Example 5 (1) Preparation of composite carrier Same as Example 1.
[0083] (2) Bimetallic atomic deposition 0.1 g g-C3N4 / rGO composite support was placed in the ALD reaction chamber. First, Sn deposition was performed at 150 °C using Sn(NMe2)4 as the tin precursor and water as the co-reactant. The deposition process consisted of 50 cycles, with each cycle following the procedure: Sn(NMe2)4 pulsed for 0.5 s, followed by argon purging for 10 s, then water vapor pulsed for 0.5 s, and finally argon purging for 10 s.
[0084] Next, the reaction chamber was switched to contain the silver precursor Ag(CF3COO), and plasma-assisted ALD of silver was performed at 130°C to achieve Ag deposition. This process used hydrogen plasma as the reducing agent, with a deposition power set to 150W, and was repeated 20 times. The procedure for a single cycle was as follows: an Ag(CF3COO) pulse was introduced for 0.5 seconds, followed by argon purging for 10 seconds, then a plasma (H2) pulse was introduced for 0.5 seconds, followed by argon purging for 10 seconds.
[0085] Finally, the sample after the above deposition treatment was transferred to a tube furnace for reduction annealing in an H2 atmosphere. The annealing procedure was as follows: heating to 250°C at a heating rate of 5°C / min and holding at this temperature for 30 min to obtain the bimetallic supported catalyst Ag / Sn / g-C3N4 / rGO, denoted as ASNC-5. ICP-MS analysis showed that the total bimetallic content in ASNC-5 was 3.5 wt%, and the ratio of Ag to Sn atoms was 1:2.5.
[0086] Example 6 The catalyst Ag / Sn / g-C3N4 / rGO was prepared according to the method in Example 1, except that in step (2), Ag was first cyclically deposited, and then Sn was cyclically deposited. The prepared catalyst Ag / Sn / g-C3N4 / rGO was designated ASNC-6.
[0087] Example 7 The catalyst Ag / Sn / g-C3N4 / rGO was prepared according to the method in Example 1, except that in step (2), the number of Sn deposition cycles was controlled to be 100 and the number of Ag deposition cycles was controlled to be 40. The prepared catalyst Ag / Sn / g-C3N4 / rGO was designated ASNC-7. ICP-MS analysis showed that the total bimetallic content in ASNC-7 was 7.0 wt%, and the atomic ratio of Ag to Sn atoms was 1:2.5.
[0088] Example 8 (1) Preparation of composite carrier 3g of the obtained g-C3N4 nanosheets were added to 300mL of an aqueous dispersion of graphene oxide (GO) with a concentration of 3g / L. The mixture was ultrasonically treated at 150W for 20min using an ultrasonic cell disruptor to ensure thorough mixing. Subsequently, the mixture was transferred to a reaction vessel and hydrothermally reacted at 180℃ for 6 hours to reduce GO to rGO. After the reaction was completed, the product was filtered, washed, and dried to obtain the g-C3N4 / rGO composite support.
[0089] (2) Bimetallic atomic deposition 0.1 g g-C3N4 / rGO composite support was placed in the ALD reaction chamber. First, Sn deposition was performed at 140 °C using Sn(NMe2)4 as the tin precursor and water as the co-reactant. The deposition process consisted of 80 cycles, with each cycle following the following procedure: Sn(NMe2)4 pulse for 0.5 s, followed by argon purging for 10 s, then water vapor pulse for 0.5 s, and finally argon purging for 10 s.
[0090] Next, the reaction chamber was switched to use the silver precursor Ag(hfac)(COD), and plasma-assisted ALD of silver was performed at the same temperature to achieve Ag deposition. This process used hydrogen plasma as the reducing agent, with a deposition power set to 150W, and was repeated for 35 cycles. The procedure for a single cycle was as follows: an Ag(hfac)(COD) pulse was introduced for 0.5 s, followed by argon purging for 10 s, then a plasma (H2) pulse for 0.5 s, and finally argon purging for 10 s.
[0091] Finally, the sample after the above deposition treatment was transferred to a tube furnace for reduction annealing in an H2 atmosphere. The annealing procedure was as follows: heating to 250°C at a heating rate of 5°C / min and holding at this temperature for 30 min to obtain the bimetallic supported catalyst Ag / Sn / g-C3N4 / rGO, denoted as ASNC-8. ICP-MS analysis showed that the total bimetallic content in ASNC-8 was 4.3 wt%, and the ratio of Ag to Sn atoms was 1:2.3.
[0092] Comparative Example 1 0.1 g g-C3N4 nanosheet powder composite support was placed in the ALD reaction chamber, and tin precursor Sn(NMe2)4 was introduced. Ar was used as the carrier gas and purging gas. 50 Sn deposition cycles were performed at 150 °C. The operation procedure for a single cycle was as follows: Sn(NMe2)4 was first pulsed for 0.5 s, then argon was introduced for 10 s purging, then water vapor was pulsed for 0.5 s, and then argon was introduced for 10 s purging. Next, the silver precursor Ag(hfac)(COD) was switched to, and 20 Ag cycle depositions were performed at the same temperature. The operation procedure for a single cycle was as follows: first, Ag(hfac)(COD) was pulsed for 0.5s, then argon was purged for 10s, then plasma (H2) was pulsed for 0.5s, and then argon was purged for 10s.
[0093] Finally, the sample after the above deposition treatment was transferred to a tube furnace and subjected to reduction annealing in an H2 atmosphere. The annealing procedure was as follows: heating to 250°C at a heating rate of 5°C / min and holding at this temperature for 30 min to obtain the bimetallic supported catalyst Ag / Sn / g-C3N4, denoted as ASN.
[0094] Comparative Example 2 200 mL of an aqueous dispersion of graphene oxide (GO) with a concentration of 3 g / L was added to a reaction vessel and hydrothermally reacted at 180 °C for 6 hours. During this process, GO was reduced to rGO. After the reaction was completed, the product was filtered, washed and dried to obtain rGO powder.
[0095] 0.1 g rGO powder was placed in the ALD reaction chamber, and tin precursor Sn(NMe2)4 was introduced. Ar was used as the carrier gas and purging gas. 50 deposition cycles were performed at 150 °C. The operation procedure for a single cycle was as follows: Sn(NMe2)4 was first pulsed for 0.5 s, then argon was purged for 10 s, then water vapor was pulsed for 0.5 s, and then argon was purged for 10 s.
[0096] Next, the silver precursor Ag(hfac)(COD) was switched to and 20 cycles of deposition were performed at the same temperature. The operation procedure for a single cycle was as follows: Ag(hfac)(COD) pulse was introduced for 0.5s, followed by argon purging for 10s, plasma (H2) pulse was introduced for 0.5s, and then argon purging was performed for 10s.
[0097] Finally, the sample after the above deposition treatment was transferred to a tube furnace and subjected to reduction annealing in an H2 atmosphere. The annealing procedure was as follows: heating to 250°C at a heating rate of 5°C / min and holding at this temperature for 30 min to obtain the bimetallic supported catalyst Ag / Sn / g-C3N4, denoted as ASC.
[0098] Comparative Example 3 (1) Preparation of composite carrier Same as Example 1.
[0099] (2) Bimetallic atomic deposition 0.1 g of g-C3N4 / rGO composite support was placed in the ALD reaction chamber, and silver precursor Ag(CF3COO) was introduced. 70 cycles of deposition were performed at the same temperature. The procedure for each cycle was as follows: a 0.5 s pulse, followed by 10 s argon purging, then a 0.5 s plasma (H2) pulse, followed by 10 s argon purging. Finally, reduction annealing was performed at 250 °C for 30 min in an H2 atmosphere to obtain the silver-supported catalyst Ag / g-C3N4 / rGO, denoted as ASNC-D3.
[0100] Comparative Example 4 This comparative example uses a chemical reduction method to prepare the catalyst Ag / Sn / g-C3N4 / rGO.
[0101] (1) Preparation of composite carrier Same as Example 1.
[0102] (2) Loading metal Add 0.1 g g-C3N4 / rGO to 50 mL of water and sonicate for 30 min. Then, while stirring, add 0.15 mL of a 40 mmol / L AgNO3 aqueous solution and continue stirring for 30 min to disperse the Ag... +The catalyst was fully adsorbed onto the support surface. 3 mg of SnCl2 was dissolved in 1 mL of a 0.1 mol / L HCl aqueous solution, added to the aforementioned system, and stirred for 30 min. The pH of the system was then adjusted to 9–10 using a 1 mol / L NaOH aqueous solution. Next, 5 mL of a 0.1 mol / L NaBH4 aqueous solution was added, and the reaction was carried out in an ice bath for 2 h. After the reaction was complete, the solid was collected by centrifugation, washed three times with water, and finally dried under vacuum at 60 °C for 12 h to obtain the catalyst Ag / Sn / g-C3N4 / rGO, denoted as ASNC-D4.
[0103] Test case This test example is used to illustrate the performance of the catalysts prepared in the examples and comparative examples.
[0104] Catalyst ink was prepared by dispersing 20 mg of catalyst powder, 45 µL of 5% Nafion solution (purchased from DuPont, brand name D520) and 2.5 mg of carbon black in 150 µL of isopropanol. The ink was then uniformly coated onto carbon paper (coating area 1.0 cm × 1.0 cm), air-dried at room temperature, and then dried in a vacuum drying oven at 60 °C for 12 hours to obtain the catalyst electrode.
[0105] The catalyst electrode was used as the cathode, and the Pt / Ru / C composite material (Pt / Ru molar ratio of 1:1, total metal (Pt+Ru) loading of 40 wt%) was used as the anode. The components were assembled into an electrolytic cell and an electrolyte (aqueous solution of KHCO3 with a concentration of 0.5 mol / L) was injected.
[0106] CO2 gas was pumped into the electrolytic cell at a flow rate of 15 mL / min to conduct the electrocatalytic reduction reaction of CO2. Before use, CO2 gas was continuously introduced for 30 minutes to ensure the electrolyte reached CO2 saturation. Subsequently, constant-voltage electrolysis was performed at 25°C with the reaction voltage controlled at 2.3 V. The current after the system reached steady state was recorded, with a corresponding areal current density of approximately 100 mA / cm². 2 After 2 hours of electrocatalytic treatment, sampling began, and the concentrations of CO, H2, and CO2 in the cathode outlet gas were detected by gas chromatography. The CO Faradaic efficiency and CO2 single-pass conversion rate were calculated. The CO Faradaic efficiency (…) FE CO ), CO2 single-pass conversion rate ( The calculation method is as follows:
[0107]
[0108] In Equation 1, Z The number of electrons required to produce 1 mol of CO (CO2 + 2H+)+ + 2e - → CO + H2O, therefore Z=2). F It is the Faraday constant (96,485 C / mol). n Let represent the amount of CO produced (mol), and Q represent the total charge of the reaction (C), obtained by current integration.
[0109] In Equation 2, This refers to the number of moles of CO2 entering the reactor per unit time. This represents the number of moles of CO2 exported, i.e., the amount of unreacted CO2.
[0110] Catalytic activity stability test: The catalytic reaction time was extended to 100h to evaluate stability. Samples were taken every 10h after the reaction started (sampling time points: t = 10, 20, 30, ..., 100h). After each sampling, the CO Faraday efficiency and CO2 single-pass conversion rate were calculated simultaneously.
[0111] Stability criterion: Stability is defined as simultaneously satisfying ≥10%, FE CO The duration when ≥90% of the time is recorded as stability > 100h if the above criteria are still met at t = 100h; if the above criteria are not met for the first time in the nth sampling (n×10h, where n is an integer from 1 to 10), then stability < n×10h.
[0112] The test results are shown in Table 1.
[0113] Table 1
[0114] Based on the data in Table 1, the catalysts in Examples 1-8 exhibited a comprehensive and balanced performance improvement in the CO2 electroreduction to CO reaction. Their CO Faraday efficiency (94%-98%) and CO2 single-pass conversion rate (14.5%-18.6%) remained consistently at high levels, and no significant degradation was observed after continuous operation for over 100 hours. In contrast, the catalysts in Comparative Examples 1-4 were inferior in terms of efficiency, conversion rate, and stability.
[0115] Therefore, the catalysts in Examples 1-8 can continuously and efficiently convert CO2 to CO with low energy consumption (2.3 V cell pressure). This advantage is directly reflected in the two-step process of "CO2 electroreduction to CO to CO thermocatalytic methanol production": the highly selective, high single-pass conversion rate, and continuously stable CO product obtained in the first step can not only significantly reduce the energy consumption and cost of subsequent gas separation and purification, but also provide a stable feed gas with few impurities for the second step of thermocatalytic hydrogenation, thereby improving the overall yield and process economy of methanol synthesis.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing an electrocatalyst for CO2 reduction, characterized in that, include: A bimetallic active component is loaded onto a composite support using an atomic layer deposition process. The bimetallic active component is silver and tin, and the composite support comprises graphitic nitrogen carbide nanosheets and reduced graphene oxide. In the composite carrier, the mass ratio of graphitic nitrogen carbide nanosheets to reduced graphene oxide is (1.5~5):1; In the bimetallic active component, the atomic ratio of silver to tin is 1:(2~3); The steps for loading metal active components using atomic layer deposition include: (a) Deposition of the first metal atomic layer The reaction chamber containing the composite support is heated to 100-180°C, and the first metal deposition cycle is repeated 40-100 times using an inert gas as both carrier and purge gas. Each cycle includes: First, a pulse of the first metal precursor is introduced into the reaction chamber, then the reaction chamber is purged with inert gas, then a pulse of the corresponding reactant is introduced into the reaction chamber, and finally the reaction chamber is purged with inert gas. (b) Deposition of the second metal atomic layer Maintain the reaction chamber temperature at 100~180℃ and an inert atmosphere, switch to the second metal precursor, and repeat the second metal deposition cycle 20~40 times. Each cycle includes the following steps: First, a second metal precursor pulse is introduced into the reaction chamber, then the reaction chamber is purged with inert gas, then a corresponding reactant pulse is introduced into the reaction chamber, and finally the reaction chamber is purged with inert gas. (c) The product obtained in step (b) is subjected to reduction annealing in a hydrogen-containing atmosphere to form the bimetallic active component on the composite support; wherein The first metal precursor is a tin precursor, the second metal precursor is a silver precursor, the corresponding reactant pulse of the tin precursor is an oxygen-containing source pulse, and the corresponding reactant pulse of the silver precursor is a plasma pulse.
2. The preparation method according to claim 1, characterized in that, In the electrocatalytic CO2 reduction catalyst, the loading of the bimetallic active component is 1% to 10%.
3. The preparation method according to claim 1, characterized in that, The process also includes the following steps for preparing the composite support: The graphitic carbon nitride nanosheets and graphene oxide dispersions are mixed and ultrasonically dispersed, followed by a hydrothermal reaction to convert the graphene oxide into reduced graphene oxide, thereby obtaining the composite carrier.
4. The preparation method according to claim 3, characterized in that, The hydrothermal reaction is carried out at a temperature of 150-200℃ for 5-15 hours.
5. The preparation method according to any one of claims 1-4, characterized in that, The graphitic carbon nitride nanosheets were prepared according to the following steps: Pyrolysis of nitrogen-containing organic matter forms bulk graphitic carbon nitride; The bulk graphitic carbon nitride is dispersed in a solvent and then ultrasonically exfoliated to form graphitic carbon nitride nanosheets.
6. The preparation method according to claim 5, characterized in that, The nitrogen-containing organic compound is selected from at least one of melamine, urea, thiourea, cyanamide, and dicyandiamide.
7. The preparation method according to claim 5, characterized in that, The pyrolysis process includes: heating the nitrogen-containing organic matter to 450-600°C at a rate of 5-10°C / min and holding it at that temperature for 1-5 hours.
8. The preparation method according to claim 5, characterized in that, In the ultrasonic ablation process, the concentration of the bulk graphitic carbon nitride in the solvent is 5-10 g / L, and the ultrasonic ablation power is 150-300 W, with a time of 5-10 h.
9. The preparation method according to any one of claims 1-4, characterized in that, The reduction annealing temperature is 200~400℃, and the time is 10~60min.
10. The preparation method according to claim 1, characterized in that, The silver precursor is Ag(hfac)(COD) and / or Ag(CF3COO).
11. The preparation method according to claim 1, characterized in that, The plasma source of the plasma pulse includes hydrogen and an optional carrier gas, and the plasma power is 100~250W.
12. The preparation method according to claim 1, characterized in that, During the deposition of silver atomic layers, the duration of the silver precursor pulse in each cycle is 0.2–0.8 s, the duration of the plasma pulse is 0.2–0.8 s, and the duration of each inert gas purging is 5–15 s.
13. The preparation method according to claim 1, characterized in that, The tin precursor is at least one of Sn(NMe2)4, SnCl4, SnCl2 and Sn(CH3)4.
14. The preparation method according to claim 1, characterized in that, The oxygen source of the oxygen source pulse includes water vapor and optional carrier gas.
15. The preparation method according to claim 1, characterized in that, During the tin atomic layer deposition process, the duration of the tin precursor pulse in each cycle is 0.2~0.8s, the duration of the oxygen source pulse is 0.2~0.8s, and the duration of each inert gas purging is 5~15s.
16. An electrocatalyst for CO2 reduction prepared by any one of claims 1-15.
17. The application of the electrocatalyst for CO2 reduction according to claim 16 in the electrocatalyst reduction of CO2 to produce CO or in a two-step process for producing methanol from CO2; wherein, The two-step method includes: The first step is the electrocatalytic reduction of CO2 to produce CO; The second step involves preparing methanol from the prepared CO via thermocatalytic hydrogenation.